PENGARUH KOMUNIKASI CAMAT TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PABUARAN KABUPATEN CIREBON - Dewi Roekmana; Mukarto Siswoyo; Agus Supriyadi (Universitas Swadaya Gunung Jati, 2018)
ABSTRACTResearch by the author is Camat Communicatian influence on employee performance at the district office Pabuaran Cirebon Regency.Methods of research by the author is quantitative research methods, here the start of data collection, data interpretation, until the results of research using number..Issues the author is employee performance at the district office Pabuaran Cirebon Regency is not maximized, the problem allegedly caused by non-optimal implementation of communication Camat Pabuaran county districts Cirebon.The research question posed is as follos “allegedly contained a positive and significan influence beteen communication Camat to employee performance at the district office Pabuaran Cirebon district”.Of these hypotheses can be formulated statistical hypothesis is : Ho (the null hypothesi) : rxy is calculated ≤ from rxy table, then the formulation of the problem is “there is no positive and significant influence beteen communication Camat to emplotee performance at the district office Pabuaran Cirebon regency”.And Ha (Alternative Hypothesis) : Rxy is calculated > from the rxy table, then he formulation of the problem is “there is a positive and significant influence beteen communication Cama to employee performance at the district office Pabuaran Cirebon regency.”The results shoed that the communication made by Camat districts Pabuaran Cirebon district has been quite good, but not optimal, as seen from the success of communication that reaches 65% ith a total score of 1403, and the employee’s performance is quite good but not optimal as it reaches 67,5% ith a total score of 1459.Implementation of commnication sub-district head has strong influence on the performance of employees at the district office Pabuaran district of Cirebon to the value of 0,679 and rxy is calculated ith a precision of 5% at 0,381. Because rxy count is greater then rxy table, then there is a positive and significant influence beteen communication Camat to employee performance at the district office Pabuaran Cirebon regency. Ths Ho (the null hypothesis) refused and Ha (alternative hypothesis) is accepted